2014
DOI: 10.1111/bpa.12181
|View full text |Cite
|
Sign up to set email alerts
|

CADASIL and CARASIL

Abstract: CADASIL and CARASIL are hereditary small vessel diseases leading to vascular dementia. CADASIL commonly begins with migraine followed by minor strokes in mid-adulthood. Dominantly inherited CADASIL is caused by mutations (n > 230) in NOTCH3 gene, which encodes Notch3 receptor expressed in vascular smooth muscle cells (VSMC). Notch3 extracellular domain (N3ECD) accumulates in arterial walls followed by VSMC degeneration and subsequent fibrosis and stenosis of arterioles, predominantly in cerebral white matter, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
148
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(152 citation statements)
references
References 140 publications
(292 reference statements)
3
148
0
1
Order By: Relevance
“…The TGFβ family implication in fibrosis is most interesting as fibrotic thickening of small vessels in CADASIL is widely reported 38. It has been suggested that the damage of VSMCs in CADASIL induces secondary fibrosis with consequent thickening of the walls and narrowing of the lumen of cerebral arteries 19. In this study, we found elevated expression level of TGF β isoforms ( TGF β 1, TGF β 2 and TGF β 3 ) in Pla‐ and CerVSMCs, where the increased level of TGF β 3 was more obvious as compared to the TGF β 1 or TGF β 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TGFβ family implication in fibrosis is most interesting as fibrotic thickening of small vessels in CADASIL is widely reported 38. It has been suggested that the damage of VSMCs in CADASIL induces secondary fibrosis with consequent thickening of the walls and narrowing of the lumen of cerebral arteries 19. In this study, we found elevated expression level of TGF β isoforms ( TGF β 1, TGF β 2 and TGF β 3 ) in Pla‐ and CerVSMCs, where the increased level of TGF β 3 was more obvious as compared to the TGF β 1 or TGF β 2 .…”
Section: Discussionmentioning
confidence: 99%
“…NOTCH3 is a type I transmembrane receptor belonging to the Notch signalling family, one of a group of “elite” intracellular signalling pathways 17, 18. Currently, more than 230 different CADASIL‐causing mutations in the NOTCH3 gene have been detected,19 which are either missense mutations or small in‐frame deletions in the epidermal growth factor repeats of NOTCH3 . These mutations affect the number of cysteine residues, leading to an unpaired cysteine residue 20, 21, 23, 24…”
Section: Introductionmentioning
confidence: 99%
“…Eventually, multiple strokes cause gait problems, urinary incontinence, depression, and pseudobulbar palsy. 45,46 Leukoaraiosis Leukoaraiosis was derived from the Greek words for 'white' and 'rarified', and was originally proposed to describe the low signal seen on CT in the white matter for which a concise etiology was lacking. 47 The attenuated signal on CT corresponds to high signal on T2-weighted MRI.…”
Section: Inherited Forms Of Small Vessel Diseasementioning
confidence: 99%
“…Within CVD, the most common contribution is likely central SVD, which involves tissue injury in both cortical and subcortical gray and white matter, but may coexist with atherosclerosis involving large extracranial vessels and embolic disease [4,17,41]. Vessel wall changes such as arteriolosclerosis and CAA were proposed to be the most earliest and common changes, followed by perivascular spacing with lacunar and regional microinfarcts progressing from frontal to temporal lobe and basal ganglia [52].…”
Section: Pathogenesis Of Cvi/vadmentioning
confidence: 99%